2011
DOI: 10.1111/j.1365-3016.2011.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

International migration and gestational diabetes mellitus: a systematic review of the literature and meta‐analysis

Abstract: Influxes of migrant women of childbearing age to receiving countries have made their perinatal health status a key priority for many governments. The international research collaboration Reproductive Outcomes And Migration (ROAM) reviewed published studies to assess whether migrants in countries of resettlement have a greater risk of gestational diabetes mellitus (GDM) than women in receiving countries. A systematic review of the literature from Medline, Embase, PsychInfo and CINAHL from 1990 to 2009 included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 61 publications
4
40
1
8
Order By: Relevance
“…There were no studies identified examining determinants of caesareans in migrants specifically. However, gestational diabetes mellitus (GDM) and feto-pelvic disproportion are known to complicate delivery and increase the risk of caesarean [104,105] and these are more common in some migrant women [28,39,106]. Reasons for increased risk of GDM in migrants are unknown but might be associated with a genetic pre-disposition, or physiological response to dietary changes; the involvement of a stress response has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…There were no studies identified examining determinants of caesareans in migrants specifically. However, gestational diabetes mellitus (GDM) and feto-pelvic disproportion are known to complicate delivery and increase the risk of caesarean [104,105] and these are more common in some migrant women [28,39,106]. Reasons for increased risk of GDM in migrants are unknown but might be associated with a genetic pre-disposition, or physiological response to dietary changes; the involvement of a stress response has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes screening was carried out only in 80.8 % of the AIW compared with 99.4 % of native-born mothers. As evidenced in a recent meta-analysis, immigrant women from Africa are more likely to develop gestational diabetes mellitus than their native-born peers [9]. Gestational diabetes mellitus is also a known risk factor in delivering macrosomic newborns [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that more than half of female immigrants are of reproductive age, which means that many of their social and health needs concern reproduction and maternity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This figure represents approximately 4.5-5.0% of all births, although specific groups are at greater risk of developing this disorder [1]. GDM rates have increased dramatically in the past twenty years [2-4] and this pattern of increase appears to relate primarily to the obesity epidemic [5], increasing maternal age [4,6], and migration from high risk areas, such as South East Asia [7]. In Australia, highest rates of GDM are reported among women born in Polynesia, Asia, South Asia (Indian subcontinent) and the Middle East.…”
Section: Introductionmentioning
confidence: 99%